Lessons towards rights-responsive REDD+ safeguards from a literature review - Lofts, K.; Sarmiento Barletti, J.P.; Larson, A.M. (Center for International Forestry Research, 2021)
Safeguards for REDD+ arose in response to serious concerns voiced by forest-dependent Indigenous Peoples and local communities, and non-governmental organizations, over its potential to infringe upon their rights and territories. Several institutions have also developed voluntary standards for REDD+, in addition to safeguards guidelines adopted by multilateral funding institutions. This working paper examines safeguards experiences in REDD+ and other natural resource management initiatives to understand when safeguards work, for whom, and why. It seeks to extract lessons for rights-responsive safeguards standards and guidelines to protect and support the rights of Indigenous Peoples and local communities, and the women within those groups. This work, carried out under CIFOR’s Global Comparative Study on REDD+, is part of a series on REDD+ safeguards, focusing on the rights and social inclusion concerns of the women and men of the Indigenous Peoples and local communities that steward the forests where climate solutions are implemented.